2018
DOI: 10.1248/bpb.b17-00750
|View full text |Cite
|
Sign up to set email alerts
|

<i>Nardostachys jatamansi</i> Ethanol Extract Ameliorates Aβ42 Cytotoxicity

Abstract: SummaryThe Nardostachys jatamansi DC (NJ) root has been used as a sedative or analgesic to treat neurological symptoms and pain in traditional Korean medicine. Here, we investigate the potential effects of NJ on Alzheimer's disease (AD) and reveal the molecular mechanism through which NJ exerts its effects. The neuroprotective effect of the NJ root ethanol extract against β amyloid (Aβ) toxicity was examined in vitro using a cell culture system and in vivo using a Drosophila AD model. The NJ extract and chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Among the tested, six terpenes, including ρ-cymene, limonene (+), limonene (−), linalool, α-pinene (+), and β-pinene (−) were shown to relieve the rough eye phenotype when fed to Previously, we reported that ectopic expression of Aβ42 in neurons decreased the survival rate of flies during development. [21][22][23] Therefore, we conducted a secondary screening to observe if feeding the selected terpenes would increase the survival rate of the flies expressing Aβ42 in neurons during the developmental stage. The survival rate of the Drosophila was measured in duplicate after being fed with low concentrations (50 µg/mL) and high concentrations (200 µg/mL) of the six terpenes selected during the first screening.…”
Section: Screening the Terpenes That Alleviate The Phenotypes Of The mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the tested, six terpenes, including ρ-cymene, limonene (+), limonene (−), linalool, α-pinene (+), and β-pinene (−) were shown to relieve the rough eye phenotype when fed to Previously, we reported that ectopic expression of Aβ42 in neurons decreased the survival rate of flies during development. [21][22][23] Therefore, we conducted a secondary screening to observe if feeding the selected terpenes would increase the survival rate of the flies expressing Aβ42 in neurons during the developmental stage. The survival rate of the Drosophila was measured in duplicate after being fed with low concentrations (50 µg/mL) and high concentrations (200 µg/mL) of the six terpenes selected during the first screening.…”
Section: Screening the Terpenes That Alleviate The Phenotypes Of The mentioning
confidence: 99%
“…Suppression of Aβ42-Induced Cell Death in Drosophila AD Models by Limonene (+) Feeding Previously, we reported that both the rough eye phenotype and decrease in viability in Aβ42-expressing flies have been associated with cell death. 22,28) Therefore, we investigated if limonene (+) is able to inhibit cell death by observing its ability to alleviate both the rough eye phenotype and decrease in viability. Drosophila expressing Aβ42 in neurons or the developing eyes were raised in a medium containing limonene (+) (200 µg/mL), and then subjected to AO staining of their brains or the imaginal discs.…”
Section: Screening the Terpenes That Alleviate The Phenotypes Of The mentioning
confidence: 99%
“…Recently, several biological effects of the extracts from this species were reported. For instance, the ethanol extracts were shown to protect against β- amyloid-induced toxicity in SH-SY5Y cells [ 2 ]. The aqueous extracts also exhibited protective effects against 2K1C-induced cardiac hypertrophy in a rat model [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the findings of natural alternative potent therapeutic interventions are very important to overwhelm these complications permanently. Growing evidence suggests that medical plants or herbals extracts and their components have been shown to possess potent anti‐inflammatory, anti‐viral and neuroprotective functional properties that increase use of these plant products against several diseases (Cui et al, 2010; Liu et al, 2018; Seoposengwe, van Tonder, & Steenkamp, 2013; Vasiadi et al, 2014). Santalum album ( S. album ) is an indigenous medicinal plant that commonly known as sandalwood in Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%